2006
DOI: 10.1007/s10530-006-9060-2
|View full text |Cite
|
Sign up to set email alerts
|

First report of the Asian seaweed Sargassum filicinum Harvey (Fucales) in California, USA

Abstract: We report the occurrence of the brown seaweed Sargassum filicinum Harvey in southern California.Sargassum filicinum is native to Japan and Korea. It is monoecious, a trait that increases its chance of establishment. In October 2003, Sargassum filicinum was collected in Long Beach Harbor. In April 2006, we discovered three populations of this species on the leeward west end of Santa Catalina Island. Many of the individuals were large, reproductive and senescent; a few were small, young but precociously reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 9 publications
0
38
0
1
Order By: Relevance
“…Most thalli detach before maturation due to the positive buoyancy of the vesicles. In the East China Sea, S. horneri was found to detach from the Chinese coasts of Zhejiang Province between January and March, and the floating biomass transported to the fringes of the continental shelf towards waters influenced by the Kuroshio Current from March to May (Komatsu et al 2007(Komatsu et al , 2008Lin et al 2017;Qi et al 2017).…”
Section: Source Of the Floating Sargassum Biomass In The Yellow Seamentioning
confidence: 99%
See 1 more Smart Citation
“…Most thalli detach before maturation due to the positive buoyancy of the vesicles. In the East China Sea, S. horneri was found to detach from the Chinese coasts of Zhejiang Province between January and March, and the floating biomass transported to the fringes of the continental shelf towards waters influenced by the Kuroshio Current from March to May (Komatsu et al 2007(Komatsu et al , 2008Lin et al 2017;Qi et al 2017).…”
Section: Source Of the Floating Sargassum Biomass In The Yellow Seamentioning
confidence: 99%
“…In addition, research has shown S. horneri to expand its distribution from the coasts of East Asia to the American coasts, spreading along the coasts of southern California and down into Baja California, Mexico. This is most likely the result of natural dispersal methods such as seaweed rafts or due to human activities such as shipping (Miller et al ; Kaplanis et al ).…”
mentioning
confidence: 99%
“…However, the extraordinarily high pairwise divergence within Ishige (Cho et al 2004) led us to further work. The cox3 is a mitochondrial protein-encoding gene, the utility of which has been recently tested for three brown algae: Scytosiphon lomentaria (Kogame et al 2005), Sargassum filicinum (Miller et al 2007), and Undaria pinnatifida (Uwai et al 2006). The plastid rbcL gene is frequently used for elucidation of the taxonomy and phylogeny of many brown algae (e.g., Cho et al 2004).…”
mentioning
confidence: 99%
“…Furthermore, the recent discovery of Sargassum horneri in 2003 in southern Californian waters (Miller et al . ) was also not acted upon; while this species remained in relatively low abundances and at only a few specific locations along this coast through ~2012, it has now become widespread throughout much of southern California (J. R. Smith, personal observation).…”
Section: Discussionmentioning
confidence: 99%
“…In southern California, it is clear that a rapid response was not undertaken either with Sargassum muticum, first detected in the region in the 1970s, or with the red alga Caulacanthus ustulatus, first detected in 1999 and now common throughout the region (Smith et al 2014). Furthermore, the recent discovery of Sargassum horneri in 2003 in southern Californian waters (Miller et al 2007) was also not acted upon; while this species remained in relatively low abundances and at only a few specific locations along this coast through~2012, it has now become widespread throughout much of southern California (J. R. Smith, personal observation).…”
Section: Eradication Of Sargassum Muticummentioning
confidence: 99%